The Impact of Social Media and Its Influence in the World of Education - Laros Tuhuteru; Imman Yusuf Sitinjak; Tukiyo Tukiyo; Rosita Nainggolan; Hermans Gavin (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Advances in information technology in the current era of globalization is very rapid. The progress of information technology is marked by the ease in finding and receiving information, especially in the world of education. So that technology can be used as a tool for students in the world of education by utilizing the internet. The internet is a medium that provides many facilities, one of which is social media. Social media is a means of information and communication that has many impacts and influences in the world of education, both positive and negative impacts. In line with that this research aims to find out the impact of social media and its influence in the world of education. The method used by researchers in this study is a quantitative method using a survey model using Google forms and in-depth interviews with several students. This research was conducted at Madrasah Aliyah level students in Cirebon. The results of this study indicate that social media can have positive and negative influences and impacts in the world of education. One of the negative impacts felt by students from the use of social media in the world of education is the easy distraction of students’ concentration during the learning process.